Quantitative Analysis of the Impact of Online + Offline Intelligent Evaluation of SQL Database Algorithm on Courses - Tian, Hu (2022 4th International Conference on Inventive Research in Computing Applications (ICIRCA), 2022)
As a highly specialized subject, the large-scale database application course plays a very important role in the social and economic development of our country. From the current point of view, the traditional teaching system of large-scale database application courses can no longer meet the development needs of the era of big data. Analyze the video attraction of online courses. Through statistical analysis, establish a single video attraction factor R, and study the attraction of a single video based on multiple regression algorithms Mathematical mechanism that force is affected by video attributes. It is found that the attractiveness of a single video is negatively linearly related to both video duration and video release time. Judge the relative importance of the curriculum, and then explore the establishment of a quantitative evaluation model for the curriculum system.